A Third Space Approach to Integrated Academic Student Success Advising (ASSA). - Picton, Catherine; Jaquet, Alison; Simons, Leah; Byrne, Kaylenne; Oostergo, Natalie; Henderson, Amanda; Wood, Denise (Student Success v.15 n.1 p.35-47 https://doi.org/10.5204/ssj.2855, 2024)
The Academic Student Success Advising (ASSA) project enacted an integrated academic and pastoral approach to advising using McIntosh's (2023) fundamental principles of advising. This research conducted at two Australian universities explores how shared principles of advising can provide an underpinning structure to pan-university advising approaches as a mechanism of student development. Forty staff were interviewed, exploring understandings and experiences of advising. Data were analysed through the four key advising themes: inclusive, personalised and integrated, developmental, and student-centred. The findings suggest that staff perceive value in integrated advising approaches that connect students' academic and pastoral experiences through an 'advising as teaching lens' and that link areas of the university to enhance student success. Recommendations highlight the value of investing in staff understandings of advising to enhance student development, the intentional embedding of co-curricular skills, and the continued need to develop systems to track advising outcomes. [Author abstract]